A guide to standardise artificial contamination procedures with protozoan parasite oocysts or cysts during method evaluation, using Cryptosporidium and leafy greens as models. (April 2022) - Chalmers, Rachel M.; Katzer, Frank; La Carbona, Stephanie; Lalle, Marco; Razakandrainibe, Romy; Robertson, Lucy J.; Robinson, Guy; Šoba, Barbara; Temesgen, Tamirat; Mayer-Scholl, Anne
Abstract: Protozoan parasites have emerged as a cause of disease associated with fresh produce and berry fruits, and are of particular concern for both public health and the food industry. For example, contamination with Cryptosporidium oocysts, whether directly from faeces or through water used in food production and processing, has led to widespread foodborne outbreaks of cryptosporidiosis. The main foodstuffs implicated so far have been fresh produce (especially leafy greens), fruit juice, milk and dairy products. There is an international standard, ISO 18744:2016, based on microscopy, for the detection of oocysts from leafy green vegetables and berry fruits, but verification and validation data that have been published for this and alternative methods can be difficult to compare due to differences in artificial contamination protocols. There is a lack of reporting of the efficiency and performance of methods used in sample surveys, hampering understanding of parasite occurrence. To improve the consistency and comparability of assays and surveys reporting the results of such artificial contamination experiments, we have developed guidance for artificial contamination procedures and analysis that can be applied to food within the category fresh produce and fruits, with particular attention to leafy greens. Information gathered through an opinion survey revealed that molecular detection would be a valuable development, but that standardised methods and improved validation data were required. A market survey revealed that the provision of oocysts for artificial contamination studies has focused on meeting requirements for microscopy detection. An insight-generation workshop provided the background knowledge synthesised into best practice guidance for artificial contamination studies using either microscopical or molecular detection. This should contribute to better method development and reporting, and improved food safety. Highlights: Foodborne parasites can cause disease outbreaks, and public health concerns. Detection methods on food require artificial contamination studies for validation. A best practice guide for artificial contamination processes is provided.